2010
DOI: 10.1093/jb/mvq018
|View full text |Cite
|
Sign up to set email alerts
|

Thermostability of striated and smooth adductor muscle tropomyosins from Yesso scallop Mizuhopecten yessoensis

Abstract: The striated and smooth adductor muscle tropomyosins (TMs) of Yesso scallop Mizuhopecten yessoensis have been known to express different isoforms, but have not been characterized in detail to date. In the present study, TMs from both muscles of Yesso scallop were purified and their stabilities were compared by circular dichroism (CD) spectrometry and differential scanning calorimetry (DSC). From the CD data, the apparent melting temperature and the apparent free energy of folding at 20 degrees C were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…On the other hand, the reliability of deconvolution analysis was judged from the extinction coefficients obtained through the calculation. 19) DSC analysis. Mb was dissolved in the same medium for CD measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the reliability of deconvolution analysis was judged from the extinction coefficients obtained through the calculation. 19) DSC analysis. Mb was dissolved in the same medium for CD measurement.…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that thermal denaturation of tuna Mb proceeded through at least three major stages. Based on the extinction coefficients obtained through deconvolution analysis, 19) three-step denaturation of tuna Mb was considered to be more likely than the two-step denaturation. The helical content decreased as the temperature was raised (Fig.…”
Section: Purification Of Mbmentioning
confidence: 99%
“…The positions of the amino acid substitutions among these three isoforms are characterized by a few clusters, suggesting that these isoforms are the splicing variants, but only one protein was found in the striated muscle, whereas the opaque portion of smooth muscle contains two isoforms (Ishimoda-Takagi and Kobayashi 1987). Ozawa et al (2010) isolated the major isoform, which was identified as that reported by Hasegawa (2001). The isoform in the translucent portion located between the opaque and striated muscles seems to be the same as the major isoform in the opaque portion (Ishimoda-Takagi and Kobayashi 1987).…”
Section: Tropomyosinmentioning
confidence: 78%
“…Since the coiled-coil structure of tropomyosin unfolds by thermal treatment in a less complicated manner, the thermostability has been intensively measured for many fish species (Ochiai et al 2003(Ochiai et al , 2010aHuang et al 2004;Huang and Ochiai 2005) and also for invertebrates (Ozawa et al 2010). The decay of α-helical and coiled-coil structures can be evaluated by CD and DSC like the myosin rod.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…TM was purified from the adductor phasic and catch muscles of P. fucata (phas- ic-TM and catch-TM, respectively) as described in a previous report [9]. The phasic adductor muscle acetone powder was extracted with 10 volumes of 20 mM Tris-HCl (pH 7.5) containing 1 M KCl and 5 mM 2-mercaptoethanol overnight, followed by centrifugation at 10,000 g for 10 min.…”
Section: Purification Of Tm From Adductor Phasic and Catch Musclesmentioning
confidence: 99%